Integration of interactive whiteboard technology in teaching primary science / Lai Mei Lan - Lai , Mei Lan (2019)
The research aimed to explore science teachers’ integration of IWBT for teaching and learning in a selected fully equipped IWBT Chinese primary school. In relation to this, factors that could lead to the reluctance in the integration of IWBT were determined and an instructional guide for more effective integration of IWBT to overcome reluctance for science teaching and learning was put forward. The research utilised a qualitative case study approach. The case selected for the study was the bounded system of an a typical Chinese government aided primary school within which the use of IWBT in the science classroom was investigated. There were six teachers from standard one to standard six who participated in the study. Multiple data collection techniques were utilised. Thirteen lesson observations and six interviews were recorded after the lesson observations. The documents related to the lessons were also collected to gain more understanding about IWBT integration and for triangulation purposes. Analysis revealed that the majority of the IWBT features were not utilised by the teachers. From a technological perspective most of the science teachers only managed to use 1 to 2 features of the IWBT in their teaching and learning activities in the classrooms. The most frequently used features were the ‘freeze’ and ‘zoom in’ of the visualizer but none of the interactive whiteboard features were utilised. Four factors that emerged from the study data which may lead to reluctance in the integration of IWBT in science classrooms, were ‘Time’, ‘Training’, ‘Attitude’ and ‘Unsolved Technical Problems’. In order to overcome the reluctance in integrating IWBT in the science classroom, an IWBT instructional guide booklet for science lessons based on the topics observed during the length of the study was prepared. The instructional guide covered topics from Year 1 until Year 6 of Primary Science of the Malaysian Curriculum. The IWBT instructional guide booklet suggests ideas for more effective integration of IWBT in the science classrooms. The users of the IWBT instructional guide booklet can select the IWBT features according to classroom activities and time frames proposed in the guide. The novelty of the IWBT instructional guide booklet is that science process skills can simultaneously be infused. Finally, the richness of the data collected allowed for the formulation of a rubric specifically to assess science teachers’ TPACK elements in integrating IWBT. The TPACK model underpinned the theoretical framework of the study. This rubric could be a future tool that can be used among teachers in schools, though more testing is needed. Implications of this research as well as some suggestions for further research were put forward.